Pendampingan Pengembangan dan Penyusunan Formulir Pengelolaan Aset Tetap untuk Meningkatkan Tata Kelola Aset di Rumah Sakit Islam Ar-Rasyid Palembang - Neneng Miskiyah; Fadhya Putri Islami; Claudya Nurcahaya; Purwati; Diva Putri Sartika (Jurnal Pengabdian UntukMu NegeRI, 2026)
Fixed asset management is one of the important aspects in supporting effective, transparent, and accountable hospital governance. However, asset management at Ar-Rasyid Islamic Hospital Palembang still faces obstacles, namely the unavailability of standardized fixed asset management forms, so that the process of recording, documentation, and asset control has not run optimally. This community service activity aims to develop, compile, and implement a fixed asset management form as a supporting instrument in hospital asset management. The implementation method includes identifying partner needs, developing and preparing forms, socialization, assistance in the use of forms, and evaluation of the implementation of activities. The results of the activity show that the asset management form has been successfully prepared according to the needs of partners and can be used as a medium for recording, documentation, and asset control more systematically. Mentoring activities increase the understanding of asset management employees regarding the use of forms and contribute to supporting more effective, transparent, and accountable management of fixed assets at Ar-Rasyid Islamic Hospital Palembang.